Deepfake technologies and social engineering in online fraud forms, mechanisms, and legal challenges - Smanova, A.B.; Muratova, A.Zh.; Zhumagulova, Sh.R. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
The digital world has undergone fundamental changes through generative neural networks that are advancing at a fast pace in artificial intelligence development. Deepfake technologies enable users to generate realistic audio and video content that duplicates actual recordings. The combination of these tools with social engineering techniques makes fraudulent schemes more believable which results in financial losses and increased cybercrime activities. Multiple jurisdictions, including Kazakhstan, face challenges in creating effective legal frameworks to address these emerging technological developments. The research investigates deepfake technology and social engineering methods used in online scams while identifying legal obstacles to prevention and proposing solutions for the improvement of legislation and institutional practices. The scientific value and practical relevance of the work lie in clarifying the interaction between psychological manipulation and generative AI, as well as in providing proposals for shaping a national strategy to counter cyber threats. The methodology relies on a comprehensive analytical approach that includes the study of documented cases of synthetic media misuse, comparative analysis of international and national legislation, and assessment of preventive strategies. The findings show that deepfakes are widely applied in executive impersonation scams, circumvention of voice biometric systems, investment fraud using fabricated images of public figures, and privacy violations such as extortion. The key legal challenges include difficulties in crime qualification, authentication of digital evidence, cross-border dimensions of cyberattacks, and allocation of liability between perpetrators and online platforms. The study concludes that an integrated approach is required, combining technological tools for thedetection and labeling of synthetic media, legal reforms to strengthen criminal and procedural law, harmonization of international norms, and educational measures to improve digital literacy. This research contributes theoretical and practical foundations for a systemic response to cybercrime involving deep synthesis technologies.